2022
DOI: 10.36834/cmej.73444
|View full text |Cite
|
Sign up to set email alerts
|

COVID as a catalyst: medical student perspectives on professional identity formation during the COVID-19 pandemic

Abstract: Background: As a result of the COVID-19 pandemic, a national decision was made to remove all medical students from clinical environments resulting in a major disruption to traditional medical education. Our study aimed to explore medical student perspectives of professional identity formation (PIF) during a nationally unique period in which there was no clinical training in medical undergraduate programs. Methods: We interviewed fifteen UBC medical students (years 1-4) regarding their perspectives on PIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…An analysis of the literature showed that a significant number of studies are devoted to the problem of forming students' research skills in terms of studying various disciplines at the university:  formation of research skills in the process of studying physics, chemistry and other natural science disciplines [14,15];  features of the formation of research skills in the process of studying the liberal arts;  study of clinical disciplines in terms of the formation of research skills [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of the literature showed that a significant number of studies are devoted to the problem of forming students' research skills in terms of studying various disciplines at the university:  formation of research skills in the process of studying physics, chemistry and other natural science disciplines [14,15];  features of the formation of research skills in the process of studying the liberal arts;  study of clinical disciplines in terms of the formation of research skills [8,9].…”
Section: Methodsmentioning
confidence: 99%